An Unusual Cause of Cranial Dural Thickening - Jing Ming Yeo; Donald MacArthur; Jillian Davis; Ian Scott; Bruno Gran (Case Reports in Neurological Medicine)
We describe an unusual cause of cranial dural thickening in an elderly female with a chronic meningeal inflammatory process. A 70-year-old ethnically Chinese, Singaporean female presented with a history of chronic daily headache with no other meningeal signs. Serial MRI brains showed progressive pachymeningeal and leptomeningeal enhancement in the left frontal region with underlying vasogenic oedema, similar appearances in the right frontal region to a lesser extent, and persistent inflammatory changes in her bilateral paranasal sinuses. Investigative work-up showed a chronically raised ESR with a normal CRP, negative ANCA, and a chronically raised serum IgA kappa paraprotein. Bone marrow trephine biopsy was suggestive of a low level plasma cell disorder. Olfactory cleft biopsy showed no evidence of IgG4-related disease or vasculitis and no significant plasma cell infiltrate. Histopathological examination from a meningeal biopsy revealed a diagnosis of an en-plaque meningioma (the WHO, 2016; Grade I) causing an unusual granulomatous reaction. We discuss the radiological and histological relations of this rare form of meningioma. Clinicians can consider en-plaque meningioma in the differential diagnosis of linear dural thickening and enhancement.